Enhancing the Tribological Behavior of Lubricating Oil by Adding TiO2, Graphene, and TiO2/Graphene Nanoparticles. Issue 3 (4th May 2019) - Alghani, Waleed; Ab Karim, Mohd S.; Bagheri, Samira; Amran, Nor Amirah M.; Gulzar, M.
Abstract: This article investigates the tribological behavior of nanoparticles (NPs) of titanium dioxide anatase TiO2 (A), graphene, and TiO2 (A) + graphene added to the pure base oil group ΙΙ (PBO-GΙΙ). The morphology of these two nanostructures of TiO2 (A) and graphene was characterized by transmission electron microscopy (TEM). Oleic acid (OA) was blended as a surfactant into the formulation to help stabilize the NPs in the lubricant oil. A four-ball test rig was used to determine the tribological performance of six different samples, and an image acquisition system was used to examine and measure the wear scar diameter of the stationary balls. Field emission–scanning electron microscopy (FE-SEM) was used to examine the wear morphology. Energy-dispersive X-ray spectroscopy (EDX), element mapping, and Raman spectroscopy were employed to confirm the presence of (TiO2 (A) + graphene) and the formation of a tribolayer/film on the mating surfaces. Moreover, a 3D optical surface texture analyzer was utilized to investigate the scar topography and tribological performance. The experiments proved that adding (0.4 wt% TiO2 (A) + 0.2 wt% graphene) to the PBO-GΙΙ optimized its tribological behavior. These excellent results can be attributed to the dual additive effect and the formation of a tribofilm of NPs during sliding motion. Furthermore, the average reductions in the coefficient of friction (COF), wear scar diameter (WSD), and specific wear rate (SWR) were 38.83, 36.78, and 15.78%, respectively, for (0.4 wt% TiO2 (A) + 0.2 wt% graphene) nanolubricant compared to plain PBO-GΙΙ lubricant.